Small Animal Imaging Basics and Practical Guide - Kiessling, Fabian; Pichler, Bernd J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Small animal imaging has been recognized as an important tool in preclinical research. Nevertheless, the results of non-invasive imaging are often disappointing owing to choice of a suboptimal imaging modality and/or shortcomings in study design, experimental setup, and data evaluation. This textbook is a practical guide to the use of non-invasive imaging in preclinical research. Each of the available imaging modalities is discussed in detail, with the assistance of numerous informative illustrations. In addition, many useful hints are provided on the installation of a small animal unit, study planning, animal handling, and the cost-effective performance of small animal imaging. Cross-calibration methods, data postprocessing, and special imaging applications are also considered in depth. This is the first book to cover all the practical basics in small animal imaging, and it will prove an invaluable aid for researchers, students, and technicians.
Keywords: Medicine; Medical laboratories; Toxicology; Radiology, Medical; Medicine & Public Health; Imaging / Radiology; Laboratory Medicine; Pharmacology/Toxicology.